Work Engagement and Leadership Impact on The Performance of Millennial Employees - Firdaus; Purboyo (CV ODIS, 2021)
This study aims to test work engagement and leadership have a significant positive effect both partially and simultaneously on the performance of workers from the millennial generation. The study was held at PT. Decorindo Inti Alam Wood. The sample involved totaled 71 millennial workers, with a predetermined sample criteria technique, namely, workers born from 1980 to 1995. This calculation indicates that in 2021, the millennial generation will be in the age range of 26 to 41 years. This study is an explanation, with a quantitative approach. The survey method used an online questionnaire and measured a Likert scale. The SPSS version 23 research tool is used to perform validity and reliability checks, as well as traditional inference tests, previous to looking at multiple linear regression, hypothesis testing, and coefficient of determination. The results of the online questionnaire are 71 millennial workers, consisting of 54 males dominating the work with a percentage of 76% while millennial female workers amounted to 17 people with a percentage of 23.9%. Male millennial workers outnumber female millennial workers because the job is sometimes strenuous and involves physical strength. The findings show that all hypotheses have been proved, namely, that employee engagement and leadership have a significant positive effect on PT. Decorindo Inti Alam Wood's results, both partially and simultaneously. The effective contribution of the influence of work engagement and leadership on the performance of employees of PT. Decorindo Inti Alam Wood amounted to 45.6% while 54.4% was influenced by other variables outside of the research.